Pemanfaatan Tanda Tangan Digital Tersertifikasi di Era Pandemi - Rizki Dermawan (Jurnal Hukum Lex Generalis, 2021)
In the digital era, several things have become easy to find. For example, transacting with e-commerce so goods ordered via cell phones come directly to consumers. Likewise, the document signing process has switched to digital. To protect digital transaction activities, the government has regulated the Information and Electronic Transactions (a.k.a ITE) law and other derivatives. Knowledge of digital signatures is needed because it has consequences and responsibilities. Digital signatures that have been certified have received an electronic certificate. There are still obstacles in the application of digital signatures and hope that people’s understanding of digital signatures will improve so as to make everyday life easier.